Identificação de cônicas e quádricas utilizando o software GeoGebra - NOVAIS, Alex Júnior (2019)
The study of Analytical Geometry on conic and quadric ,in the context of High School, is a content of paramount importance, from which we use algebraic methods and symbols to solve situations in Geometry. The objective of this research is the development of some activities of analytical geometry (conic and quadratic surfaces), in Geogebra software (version 5.0), to improve education in the process of teaching and learning, obtaining better results in the teaching of Mathematics. In all the chapters are all the step-by-step constructions of each dynamic activity of conic and quadric surface developed by the software Geogebra with the theoretical part. In the rst chapter, the content of conics (ellipse, hyperbola and parabola) was portrayed. In the second chapter, the topic covered was quadratic surfaces (ellipsoid, hyperboloid and paraboloid) and, nally, in the last chapter we approached cylindrical surfaces. In the activities developed in the software we can identify the rotations and translations, in some cases, with all theoretical part with its certain parametrizations.